PHILANTHROPY IN ANCIENT TIMES: SOCIAL AND EDUCATIONAL ASPECTS - AFTYKA , LESZEK (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article presents the data of ancient times philanthropy that stemmed from community life and was a consequence of the social nature of man; in Rome, for the first time, social and educational activity was formalized, which resulted from moral and legal norms; in the Judaic religion, help to the needy was treated as one of the most important religious practices. The article discusses the most important forms of social aid in the Western antiquity. Charity, volunteering presented as important components of the social and educational activities of modern institutions. The author emphasizes the need for the formation and development of humanistic consciousness, spiritual and moral consciousness of citizens. Therefore, cooperation between educational institutions, families, non-governmental organizations, volunteer movements, charitable foundations for the expansion of active charitable activities, and the creation of a humanistic society is required.